2011
DOI: 10.1007/s11757-011-0129-0
|View full text |Cite
|
Sign up to set email alerts
|

Langfristige Folgen sexuellen Missbrauchs Minderjähriger

Abstract: Ü b e r s i c h tZusammenfassung Über die unmittelbaren Folgen sexueller Missbrauchserfahrungen in der Kindheit hinaus werden in der Forschung seit Jahrzehnten auch langfristige effekte thematisiert. Der beitrag gibt -gestützt v. a. auf reviews und Metaanalysen - einen Überblick zur befundlage. Längerfristige Folgen sexuellen Missbrauchs werden im hinblick auf eine Vielzahl somatischer, emotionaler, kognitiver, behavioraler und sozialer Merkmale analysiert. Weitere Forschungsfragen betreffen die interindividue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 135 publications
(81 reference statements)
1
4
0
1
Order By: Relevance
“…The most pressing issues being a lack of access to adequate (psycho)therapy, financial burdens, duration of court proceedings, and witness credibility assessment as well as plausibility checks. These findings are consistent with research by Görgen et al (2012) who showed, that apart from the better documented psychological and physical long-term effects of CSA financial burdens and other long-term economic consequences may play a substantial role in the process of dealing with CSA but haven't been examined in detail yet. In line with this Herman (1994) as well as Figley (2013) stated that financial, just as much as social and personal resources, are necessary for survivors to rebuild a safe environment for themselves and help them integrate their experiences in self and world.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The most pressing issues being a lack of access to adequate (psycho)therapy, financial burdens, duration of court proceedings, and witness credibility assessment as well as plausibility checks. These findings are consistent with research by Görgen et al (2012) who showed, that apart from the better documented psychological and physical long-term effects of CSA financial burdens and other long-term economic consequences may play a substantial role in the process of dealing with CSA but haven't been examined in detail yet. In line with this Herman (1994) as well as Figley (2013) stated that financial, just as much as social and personal resources, are necessary for survivors to rebuild a safe environment for themselves and help them integrate their experiences in self and world.…”
Section: Discussionsupporting
confidence: 91%
“…A factor whose influence on processing experiences of CSA has not been investigated more thoroughly are obstacles in the context of criminal investigations (Walsh et al, 2010;Görgen et al, 2012;Volbert, 2012). Some research indicates, that longduration of court proceedings, as well as the anticipation to make a statement in front of a court (in presence of the accused perpetrator), may lead to a short-term negative influence on wellbeing and slower recovery of the damage caused by the crime (Runyan et al, 1988;Volbert, 2012).…”
Section: Obstacles In Dealing With Experiences Of Csamentioning
confidence: 99%
See 1 more Smart Citation
“…The consequences and effects are diverse: Somatic symptoms, general health status, and mental illnesses are among the consequences of ACEs, as well as social consequences for affected individuals ( 3 ). These include chronic pain, musculoskeletal disorders, obesity, diabetes, cancer, and stroke ( 4 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dabei wurden Kindesmisshandlungsformen unterschiedlich definiert, operationalisiert und eigene Cut-off-Werte festgelegt, was eine Erklärung für die nach oben abweichenden Prävalenzen bei Striegel-Moore u. Kollegen[32] sein kann. Die zum Teil inkonsistenten Definitionen und Operationalisierungen der verschiedenen Formen von Kindesmisshandlung schränken die Vergleichbarkeit der Ergebnisse ein und können zu Verzerrungen führen[29,50]. Eine weitere methodische Schwierigkeit stellt die retrospektive Erhebung von Erfahrungen mit Kindesmisshandlung dar[51,52].…”
unclassified